EDUKASI PERSONAL BRANDING DALAM PENGGUNAAN MEDIA SOSIAL KEPADA ORANG TUA SISWA SD PINTAR BANDUNG - Rachmawati, Indira; Sary, Fetty Poerwita; Dudija, Nidya; Surya, Saskia Putri (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
Community Service activities are carried out face-to-face by presenting parents of SD Pintar students as target participants to link personal branding on social media, learning motivation, wise use of gadgets, and efforts to motivate elementary school students who have just finished a long vacation. This activity took place at SD Pintar Bandung involving 44 parents and 10 teachers. This activity provides an interactive and inspirational guide for participants, focusing on how to build a positive identity on social media and optimize the wise use of gadgets as learning aids. Participants are invited to understand the concept of personal branding, where social media can be a powerful platform to strengthen children's self-image and provide high learning motivation. Practical strategies in dealing with cyberspace challenges, such as using gadgets wisely so that children can focus more on learning. The results of this activity showed a positive response from the participants where they felt helped by the guidance provided and were more confident in guiding their children to face the dynamic digital world. It is hoped that this activity can provide useful insights for SD Pintar parents, have a positive impact in helping build a young generation that is highly competitive, ready to face the digital world, and passionate about achieving success in learning and life.